Mathematical Understanding and Self Confidence of Elementary School with Realistic Mathematics Education Model - Sucahyo, Eko; Kartono, Kartono; Mulyono, Mulyono (Journal of Primary Education, 2021)
Mathematical understanding is one of the important goals in learning. Students are not just memorizing but are expected to understand the concept of the subject matter itself. In developing mathematical abilities, especially mathematical understanding, students must have self-confidence in their abilities to avoid anxiety and doubt. This study aims to determine the effect of the Realistic Mathematics Education model on the mathematical understanding and self-confidence of fourth grade students. This study uses a combination method (Mixed Method) Concurrent Embedded design. The results showed that there was an effect of the Realistic Mathematics Education learning model on the mathematical understanding and self-confidence of the students who were shown to have successfully completed the mathematical understanding of 25 out of 30 students. Meanwhile, students who got individual scores 70 or 83.33% of the proportion who achieved the above mastery at least were 75% classically. The average mathematical understanding using Realistic Mathematics Education learning model with an average result percentage of 82.00%. Students' self-confidence influences mathematical understanding by 43.5% and 56.5% is influenced by other factors. Based on the results of the study, it can be concluded that the Realistic Mathematics Education model has a strong influence on students' mathematical understanding and self-confidence in elementary schools.